2011
DOI: 10.1111/j.1708-8240.2011.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Low‐Intensity Red Laser for Activating a Bleaching Gel and Its Effect in Temperature of the Bleaching Gel and the Dental Pulp

Abstract: Bleaching gel activation with low-intensity red laser was capable of increasing the effectiveness of bleaching treatment and did not increase pulp temperature to levels deleterious to the pulp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
3
Order By: Relevance
“…The addition of colorants may help to provide a better absorption of high power diode laser light in the bleaching gel and less transmission towards the pulp chamber. Pleffken et al [ 26 ] demonstrated that a low-intensity red diode laser (660 nm) (50 mW-3 × 180 s) with a green-coloured bleach gel resulted in not more than a 2.3°C temperature elevation in the pulp chamber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of colorants may help to provide a better absorption of high power diode laser light in the bleaching gel and less transmission towards the pulp chamber. Pleffken et al [ 26 ] demonstrated that a low-intensity red diode laser (660 nm) (50 mW-3 × 180 s) with a green-coloured bleach gel resulted in not more than a 2.3°C temperature elevation in the pulp chamber.…”
Section: Resultsmentioning
confidence: 99%
“…The use of a low-intensity red diode laser (660 nm, 35% HP) with a green-coloured bleach gel resulted in a change of colour (Δ E was increased from 5.4 to 7.2 after 1 week) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…18 Ağartma işlemlerinde diyot lazer uygulamasının etkinliğini ölçen birçok çalışma yapılmıştır. 8,18,19 Kiomars ve ark., farklı dalga boylarına sahip diyot lazerin etkinliklerini değerlendirdikleri çalışmalarında, farklı dalga boylarında diyot lazer ile ağartmanın benzer sonuçlar verdiğini belirtmişlerdir. 20 Bu çalışmada, önceki çalışmalardan referans alınarak, ağartma ajanının etkinliğini artırmak için 810 nm dalga boyunda bir diyot lazer 1,5 W güçte 30 sn uygulanmıştır.…”
unclassified
“…Bu sebeple son yıllarda diş beyazlatma tedavisi estetik diş hekimliğinin en hızlı büyüyen bölümlerinden biri haline gelmiştir. 1 Araştırmalar beyazlatma ajanlarının parçalanma hızını, absorbsiyonunu ve oluşan serbest oksijen radikalleri sonucu renklenmiş moleküllerin parçalanması hızlandırmak amacı ile çeşitli aktivatör ışık kaynakları üzerine odaklanmıştır. 2 Bu nedenle son yıllarda ofiste beyazlatma tekniğinde, kompozit rezinlerde kullanılan ışık kaynakları, konvansiyonel halojen ışık kaynakları, plazma ark ışık kaynakları, lazer ve light-elimination diode (LED) gibi ışık kaynakları kullanılmasında gelişmeler görülmektedir.…”
Section: Introductionunclassified